Effect of liver ischemic preconditioning in cirrhotic rats submitted to hepatic ischemia/reperfusion injury - Pacheco,Eduardo Garcia (2006)
PURPOSE: The main aim of this study was to determine the influence of ischemic preconditioning (IPC) on rat liver cirrhosis. METHODS: Cirrhosis was induced in Wistar rats by occlusion of the hepatic duct. The animals were divided into four groups of six animals each: non-cirrhotic group (simulated operation only), cirrhotic control group (simulated operation in cirrhotic rats), I/R group (40-minute ischemia without IPC), and IPC group (cirrhotic rats with ischemia, previously submitted to IPC). The IPC procedure consisted of partial hepatic ischemia for five minutes, followed by 10 minutes of reperfusion. In the case of the IPC group, the animals were submitted to liver ischemia for 40 minutes after the preconditioning procedure, followed by 2 hours of reperfusion. Blood samples were collected for measurement of serum aminotransferases (ALT and AST). The respiratory control ratio (RCR), the mitochondrial membrane potential (MMP), and malondialdehyde (MDA) values in the hepatic tissue were analyzed. Nonparametric statistical analysis was used and a value of p<0.05 was considered statistically significant. RESULTS: Ischemia did not induce significant increase in ALT and AST levels. MDA values were significantly higher in cirrhotic animals. MMP did not significantly change in cirrhosis and liver ischemia. Mitochondrial RCR decreased in liver cirrhosis, accentuated upon liver ischemia, and did not significantly change with IPC. CONCLUSION: Ischemic preconditioning does not protect the liver from hepatic injury induced by the ischemia/ reperfusion process.